PENYUSUNAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK-EMKM) PADA AGEN - Bani Zamzami; Nuruddin Dzaky (Asosiasi Dosen Muda Indonesia, 2023)
Indonesia is a country rich in natural resources. Besides being rich in natural resources, the Indonesian population utilizes its natural resources by way of entrepreneurship. One of the very many businesses is UMKM (Micro, Small and Medium Enterprises). Setting up this business is very easy and does not require large capital. UMKM (Micro, Small and Medium Enterprises) is one of the businesses that has been established by many people, especially from the lower middle class. According to IAI in SAK EMKM Micro Small and Medium Enterprises (EMKM) are entities without significant public accountability that meet the definition and criteria of micro small businesses. Micro, Small and Medium Entities (EMKM) are used to support business activities, or business development in the future. In this study, researchers used qualitative data analysis methods. In this study describing and explaining matters related to financial reports, researchers collect data by observation, direct interviews with business owners, and make financial reports in accordance with SAK-EMKM, in the end it can show the value of Profit and Loss Reports, Reports Financial Position, Notes to Financial Statements that are more accurate.